(untitled) (Fiep Bulletin - online, 2014)
The aim of this study, is to show the elderly participation both in sports and touristic events, aging in a healthy way in search of a better quality of life. The elderly participation in nationalsports events scheduledall year round, added to their touristic interest voherever the eventsare organized, can be very significant and it can contribute effectivily for minimizing the touristc seasonal variation.